The Characteristics of Ultra-High Performance Concrete and Its Application in Structures - Zhang, Kai (Highlights in Science, Engineering and Technology, 2024)
This paper mainly introduces a new engineering material-Ultra-High performance concrete (UHPC). By adding different aggregates to the mix, UHPC has a smaller packing density and higher durability, as well as higher compressive and tensile strength and other mechanical properties. The content of silica fume and the shape of steel fiber also affect the performance of UHPC. UHPC with hooked steel fiber has higher bond strength, which improves compressive strength. Due to its enhanced durability and mechanical properties, UHPC is used in a variety of architectural and structural applications, including building structures, finishes and cladding. Based on the project background of a children’s playground platform in Chongming, Shanghai and Dongguan Binhai Bridge, this paper focuses on the application of UHPC in practical projects. The results show that the combination of steel and UHPC can provide high overall stiffness and safety. In the future, the different properties of UHPC when combined with different materials should be explored, so that UHPC can be more widely used.